Research on Green Technology Innovation Issues and Paths in the Green Development of Sichuan Counties - Xie, Wutong (International Journal of Social Sciences and Public Administration, 2024)
With the urgent need for China’s economic transformation and sustainable development, the green development of counties in Sichuan Province has become the focus of today’s society. This study aims to explore the problems and paths faced by green technology innovation in this context. First, the current status of green technology innovation in Sichuan counties is analyzed, and then the problems of green technology innovation in the green development of Sichuan counties are analyzed. The necessity of research on green technology innovation and policy coordination in Sichuan counties is emphasized, and finally the path to promote green technology innovation in Sichuan counties is proposed. Through the analysis and discussion of this study, it is expected to provide feasible technology innovation paths and policy recommendations for the green development of Sichuan counties, and promote its realization of sustainable development goals.